EMPOWERING FUTURE ENTREPRENEURS: THE MEDIATING ROLE OF PERCEIVED BEHAVIORAL CONTROL IN THE RELATIONSHIP BETWEEN ENTREPRENEURSHIP EDUCATION AND ENTREPRENEURIAL INTENTIONS - Riani, Dini; Riadi, Farid (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Entrepreneurial intention has become an important determinant of entrepreneurial behavior among university students, particularly in developing economies where graduate unemployment remains a significant challenge. This study aims to examine the effect of entrepreneurship education on entrepreneurial intention and investigate the mediating role of perceived behavioral control in this relationship. A quantitative approach was employed using a survey of undergraduate students from eight public universities in East Java, Indonesia. Data were collected from students who had completed entrepreneurship courses and analyzed using Structural Equation Modeling (SEM) with AMOS. The findings reveal that entrepreneurship education has a positive and significant effect on entrepreneurial intention and perceived behavioral control. Furthermore, perceived behavioral control significantly influences entrepreneurial intention. The mediation analysis indicates that perceived behavioral control partially mediates the relationship between entrepreneurship education and entrepreneurial intention, suggesting that entrepreneurship education strengthens entrepreneurial intention both directly and indirectly through enhancing students’ confidence in their entrepreneurial capabilities. The novelty of this study lies in integrating entrepreneurship education and entrepreneurial intention through the mediating mechanism of perceived behavioral control within the Theory of Planned Behavior framework in the context of Indonesian higher education. These findings contribute to entrepreneurship literature by providing empirical evidence of the psychological process through which entrepreneurship education fosters entrepreneurial intention. Practically, the study implies that universities should emphasize experiential and competency-based entrepreneurship learning to strengthen students’ entrepreneurial confidence and encourage entrepreneurship as a viable career choice.